Meta Analisis Pengaruh Model Problem Based Learning terhadap Hasil Belajar Siswa di SD - Ervina Anatasya (Journal on Education, 2023)
The aim of the study was to determine the effect of the PBL model on student learning outcomes in science subjects, where students are less involved in learning, so students may become bored and not concentrate during teaching-centered learning. This type ofresearch uses a literature study which is seen from the results of previousresearch. This data collection was taken from the Google Scholar journal which was made by bothgeneral authors and student research. I took five Journals (Problem Based Learning) on science learning outcomes from 2016 to2021. From the findings of the Journals it can be concluded that there is asignificant effect of Problem Based Learning on learning outcomes where theeffect is at a vulnerable of 20% to a maximum of 77%.